Comparison of minimally invasive XEN45 gel stent implantation in glaucoma patients without and with prior interventional therapies - Hengerer, Fritz; Auffarth, Gerd U.; Conrad-Hengerer, Ina (Ophthalmology and therapy, 2019)
The aim of our analysis was to compare the effectiveness of the XEN45 gel stent implantation in patients without and with prior glaucoma intervention.